Pengaruh Atraksi Wisata Terhadap Minat Wisatawan Berkunjung Ke Museum Sonobudoyo Daerah Istimewa Yogyakarta - Atiqah, Annisaa Nurul; Prakasita, Dida (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Sonobudoyo Museum is a very famous tourist destination and is often visited by tourists who come to Yogyakarta City. This study aims to determine the effect of tourist attractions (X) on visiting interest (Y) at Sonobudoyo Museum, Yogyakarta Special Region. The object of this research is tourists visiting the Sonobudoyo Museum. The method used is quantitative by taking a sample of 100 tourists who have visited the Sonobudoyo Museum. The data collection method uses a questionnaire as primary data. The data analysis technique uses the classical assumption test, namely the normality test and the multicollinearity test, as well as the multiple linear regression analysis test, the coefficient of determination test, the t test, and the f test assisted by the SPSS version 27 application. The results showed that the tourist attraction variable had a positive and significant influence on the interest in visiting the Sonobudoyo Museum. This test was carried out partially by obtaining positive and significant results. In the determination (R-Square) test results obtained 49,8% which indicates that the variable X has an effect on variable Y of 49,8%. While the remaining 50,2% is influenced by other variables. So it can be concluded that tourist attractions influence tourist interest in visiting. Tourist attractions held at the Sonobudoyo Museum include shadow puppet shows, Sonobudoyo cinema, live batik making.